Development of restoration mortars and artificial stones for use in restoring cultural heritage sites made from volcanic tuffs - Menningen, Johanna; Klein, Calvin; Pötzl, Christopher; Gross, Christian J.; Siegesmund, Siegfried (Environmental earth sciences, 2022)
Many historically significant buildings and cultural heritage sites are made of volcanic tuffs. These sites are subject to a progressive weathering and are partly in ruinous conditions. Preparing a suitable stone replacement mortar for repair work or even whole replacement stones for these rocks is of great interest. During the quarrying of tuff rocks, more than 40% of the material is rejected and cannot be further used. Utilizing this material, the production of replacement materials with optimized properties for the restoration and repair of severely damaged natural stones represents a resource-saving measure for the preservation of these buildings. In addition to the effective use of the natural stone waste, these artificial materials, in contrast to the very heterogeneous tuffs, offer a constant quality and consistent properties. A more effective exploitation can lead to a more sustainable usage of this natural resource and minimize the interference to the environment. This study describes the development of stone replacement mortars and the creation of artificial replacement stones utilizing source material from Mexico and Armenia. The resulting replacement material shows similar properties, aesthetics, and weathering behavior like the original rock, while different properties could be optimized. Petrophysical properties as well as the weathering behavior of the volcanic tuff rock were analyzed along with the developed replacement mortar and artificial stone. As hydric and thermohydric expansion processes are important factors for the durability of the investigated rocks, replacement materials were developed and optimized which, except for the pore structure of the cement and concrete matrix, show a high correspondence to the natural stones in terms of macroscopic appearance and technical properties. The compatibility of the replacement material with the original rock was investigated. Moreover, based on the evaluation of the mechanical as well as the pore space, water transport and weathering properties, the replacement stones were evaluated as equally suitable construction material, while the replacement mortars vary in regard to their results. Accordingly, the replacement stones developed in this study can be considered as full-fledged rock substitutes for the Armenian tuffs, while the replacement mortars for the Mexican tuffs partly show a good suitability and could be partially optimized.